STRATEGI SUKSES BAGI USAHA PEMASARAN JASA PENDIDIKAN BERBASIS MANAJEMEN PROSES - -, Sumaryanto (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2011)
Abstract Marketing Strategy Services Company one of them can be seen from the marketing mix are product, price, place or distribution and promotion are very helpful in marketing a product. However, in the marketing services that most directly related to the man that made a difference in the results of customer satisfaction. For the marketing of services need to consider other elements of people, physical evidence and process. Good service from service providers (people) will establish a physical evidence at the due process provision of customer services performed very well. From the physical evidence that has been formed it possible to increase the number of customers who want to use the same service. Managing Quality of Service There is a strategy that can be achieved in winning the competition with a rival business that is by delivering high quality services consistently than our competitors and higher than customer expectations. To avoid failure in service delivery, to note gaps that may occur, including the following gap between consumer expectation and management perception. Keywords: educational service marketing, management processes, customer information systems.